Теоретические подходы к конструированию моделей многовидовых кормовых агрофитоценозов на юго-востоке Украины - Глухов, А.З.; Шевчук, О.М.; Кохан, Т.П. (Промышленная ботаника, 2006)
Peculiarities of natural pasture degradation on the south-east of Ukraine are analysed. Radical improvement of the last degradation stage pastures is suggested as an effective way of biodiversity renewal. Detailed study of plant communities structure and phytocoenotic role of basic coenosis makers allowed to elaborate ecology-coenotic approach to fodder agrophytocenoses model framing. Necessity of agrophytocenoses framing in imitation of natural communities structure, where species being subordinated on phytocenotypes is proved. Opportunity of their using in composition of introduced plants from the other geographical zones is substantiated. Seven fullscale models for degradated natural communities improvement in steppe zone are worked out.